2019
DOI: 10.1016/j.cnsns.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

The Devil is in the details: Spectrum and eigenvalue distribution of the discrete Preisach memory model

Abstract: We consider the adjacency matrix associated with a graph that describes transitions between 2 N states of the discrete Preisach memory model. This matrix can also be associated with the "last-in-firstout" inventory management rule. We present an explicit solution for the spectrum by showing that the characteristic polynomial is the product of Chebyshev polynomials. The eigenvalue distribution (density of states) is explicitly calculated and is shown to approach a scaled Devil's staircase. The eigenvectors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This eigenvalue distribution exhibits a "devil's staircase"type self-similarity which is related to the self-similar structure of the mechanistic model (binary tree structure). He et al [32] and Kalmár-Nagy et al [33] reported different classes of self-similar graphs whose adjacency matrices have devil's staircase-type spectrum. In the latter paper, it was also shown that the characteristic polynomial of the adjacency matrix is a product of Chebyshev polynomials.…”
Section: The Eigenvalue Distributionmentioning
confidence: 99%
“…This eigenvalue distribution exhibits a "devil's staircase"type self-similarity which is related to the self-similar structure of the mechanistic model (binary tree structure). He et al [32] and Kalmár-Nagy et al [33] reported different classes of self-similar graphs whose adjacency matrices have devil's staircase-type spectrum. In the latter paper, it was also shown that the characteristic polynomial of the adjacency matrix is a product of Chebyshev polynomials.…”
Section: The Eigenvalue Distributionmentioning
confidence: 99%
“…He et al [20] demonstrated that the adjacency matrix for a class of symmetric tree graphs have devil's staircase type spectrum. Kalmár-Nagy et al [21] showed the same for a different type of self-similar graph, as well as that the characteristic polynomial of the adjacency matrix of such a graph is a product of Chebyshev polynomials.…”
Section: The Eigenvalue Distribution Of the Mechanistic Modelmentioning
confidence: 85%
“…Among the recent works devoted to the study of the Preisach model as applied to objects with the structure of networks and pathways, we note [52,61,62,[207][208][209]. The transition graphs describing the functioning of the discrete Preisach model were considered in relation to the problems of continuum mechanics in [210].…”
Section: Technical Systemsmentioning
confidence: 99%